Making The Black Jacobins : C. L. R. James and the Drama of History - Douglas, Rachel, 1978- (Book collections on Project MUSE., 2019)
Rachel Douglas traces the genesis, transformation, and afterlives of the different versions of C.L.R. James's landmark The Black Jacobins across the decades from the 1930s onwards, showing how James revised it in light of his evolving politics.